From Lab to Shelf: A Reliable UV Spectrophotometric Technique for Gallic Acid Analysis in Medicines and Nutraceuticals - Shoaeb Mohammad Syed,; Deepak Jadhav,; Somnath Kalegaonkar,; Ajinkya Holkar,; Satyapal Gaikwad,; Priyanka Thore, (Asian Journal of Pharmaceutical Research and Development, 2025)
The development and validation of a UV spectrophotometric technique for gallic acid are crucial to enable accurate, precise, and reliable quantification of this molecule in diverse matrices, such as medicines, herbal items, and food samples. Gallic acid, a phenolic molecule with considerable antioxidant capabilities, is frequently employed in medicinal and nutraceutical compositions. A validated UV technique offers a cost-effective, quick, and sensitive analytical tool for quality control, assuring consistency and effectiveness of goods containing gallic acid. Validation, undertaken as per ICH criteria, establishes the methods dependability by analyzing factors such as linearity, accuracy, precision, specificity, LOD, LOQ and robustness. Using distilled water as the solvent, the absorbance of gallic acid at 260 nm was measured. Over a given concentration range, the method's correlation coefficient of 0.9999 showed outstanding linearity. Following assessment, it was concluded that the validation parameters—range, accuracy, precision, limit of quantification (LOQ) recovery studies, and limit of detection (LOD)—were within reasonable boundaries. Because of its precision, accuracy, and sensitivity, the suggested approach may be used for regular analysis of gallic acid in both bulk and mixed dose forms. The pharmaceutical sector may use this approach because it is reliable and economical for quality monitoring.